2018
DOI: 10.1055/a-0603-3969
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Beta-Cell Proliferation Induced by Estradiol-17β is Foxo1 Dependent

Abstract: Estradiol-17β (E2) and the Foxo1 transcription factor have each been implicated in the regulation of β-cell proliferation. Interaction between Foxo1and estrogen receptor alpha (ERα), effecting cell cycle, has been demonstrated in breast cancer cells, but has not been studied thus far in β-cells. Using human islets and the INS1-E β-cell line, this study investigated the contribution of Foxo1 to E2-mediated β-cell replication. Foxo1 expression was knocked down in INS1-E cells using siRNA and Foxo1 activity was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…FoxO1 is a downstream effector of insulin/insulin-like growth factor-I signaling and can be regulated by Akt via phosphorylation, following nuclear exclusion (13,24). Furthermore, FoxO1 is a key regulatory factor governing a variety of physiological functions, including the pancreatic β-cells proliferation, apoptosis and autophagy (14,15,18,37). FoxO1 also protects pancreatic β-cells by inhibiting thioredoxin-interacting protein transcription (38).…”
Section: Discussionmentioning
confidence: 99%
“…FoxO1 is a downstream effector of insulin/insulin-like growth factor-I signaling and can be regulated by Akt via phosphorylation, following nuclear exclusion (13,24). Furthermore, FoxO1 is a key regulatory factor governing a variety of physiological functions, including the pancreatic β-cells proliferation, apoptosis and autophagy (14,15,18,37). FoxO1 also protects pancreatic β-cells by inhibiting thioredoxin-interacting protein transcription (38).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MAFG-AS1 and ERα may form a positive feedback loop, implying that they can promote each other to a high level of expression in ER+ breast cancer. It has been reported that FOXO1 can act as a transcription factor for ERα in breast cancer [ 40 , 41 ], which may contribute to positive feedback formation. This may also explain the mechanism of tamoxifen resistance induced by cross-talk between the cell cycle and ER signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with the findings of Vasquez et al indicating that FoxO1 expression is regulated by progesterone [31], moreover we found that estrogen is also another regulator of FoxO1 expression during implantation. A recent study also found that pancreatic beta-cell proliferation induced by estradiol-17beta is FoxO1 dependent and the authors propose a model of E2/ER-Foxo1 interactions effecting DNA synthesis, in beta-cells [41] Since few studies investigated the molecular mechanism regarding regulation of FoxO1 expression by estrogen so far, then topic needs further evaluation especially during embryo implantation and also in reproduction.…”
Section: Discussionmentioning
confidence: 99%